Participatory Approaches to Land and Sea Use Patterns: A Case Study of Yavusa Navakavu, Fiji - Bernard, Emeli; Kurniawan, Fery; Adrianto, Luky; Varo, Joeli (Coastal and Ocean Journal (COJ), 2025)
Sustainable land and sea use planning aims to balance environmental conservation with socio-economic development. This balance is particularly critical in coastal communities where traditional knowledge is plays a key role in resource management. This study examines land and sea use pattern in Yavusa Navakavu, Fiji, through participatory mapping, geospatial analysis, and landscape metrics. The results indicate that agriculture and forest cover dominate the land cover (53.85%), while the marine area is primarily used for fishing (79.91%). The forested area is characterized by a high level of landscape cohesion (99.07%) and a low level of fragmentation (Edge Density: 72.44 m/ha), indicating strong ecological connectivity and minimal urbanization pressure. The Locally Managed Marine Area (LMMA) system effectively supports conservation within the local community-based governance. However, the effects of climate change and development pressure are still significant. However, the impacts of climate change and development pressures from Suva City remain significant. Therefore, future research should incorporate high-resolution temporal data, socio-economic factors, and ecological monitoring to improve resource management and adaptive coastal planning.